2017
DOI: 10.1186/s13033-017-0156-0
|View full text |Cite
|
Sign up to set email alerts
|

Common mental disorders in asylum seekers and refugees: umbrella review of prevalence and intervention studies

Abstract: Background:In recent years there has been a progressive rise in the number of asylum seekers and refugees displaced from their country of origin, with significant social, economic, humanitarian and public health implications. In this population, up-to-date information on the rate and characteristics of mental health conditions, and on interventions that can be implemented once mental disorders have been identified, are needed. This umbrella review aims at systematically reviewing existing evidence on the preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
228
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 288 publications
(256 citation statements)
references
References 37 publications
11
228
0
6
Order By: Relevance
“…The best control condition fur such an RCT is questionable, since 7ROSES aims to increase self-efficacy, while previously established treatments (e.g. Turrini et al, 2017) for the target population primarily focus on reduction in PTSD and depression. Hence, before comparing 7ROSES to established interventions it is necessary to determine if it impacts PTSD and depression symptom levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The best control condition fur such an RCT is questionable, since 7ROSES aims to increase self-efficacy, while previously established treatments (e.g. Turrini et al, 2017) for the target population primarily focus on reduction in PTSD and depression. Hence, before comparing 7ROSES to established interventions it is necessary to determine if it impacts PTSD and depression symptom levels.…”
Section: Discussionmentioning
confidence: 99%
“…In current guideline-informed interventions (e.g., American Psychological Association [APA], 2017), little attention is paid to post-migration sources of stress which refugees experience (Miller & Rasmussen, 2010;Strang & Ager, 2010;Turrini et al, 2017), despite their impact on refugee health and well-being (Chu, Keller, & Rasmussen, 2013;Li, Liddell, & Nickerson, 2016;Porter & Haslam, 2005;Priebe, Giacco, & El-Nagib, 2016). Examples of such stressors are poverty, unsafe living conditions, loss of social network (Lambert & Alhassoon, 2015), discrimination, and insecurity about legal status (Laban, Gernaat, Komproe, van der Tweel, & De Jong, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Among other priorities, WHO's plan emphasizes the urgent need to mainstream refugee and migrant healthcare services, promote a range of short-term and long-term interventions, address the social determinants of health, and integrate mental health within refugee healthcare provision. Refugee populations exposed to war and torture have elevated rates of depression, PTSD, anxiety, chronic pain, and acute medical conditions [3][4][5][6][7]. Karen refugees from Burma have high rates of torture and war trauma related to a 70year armed conflict with the government of Burma [8], and the health effects of these experiences have been compounded by lengthy stays in refugee camps on the Thai-Burma border without legal access to medical care, education, employment, or adequate food [9].…”
Section: Introductionmentioning
confidence: 99%
“…Few trials exist in the field of refugee health due to the ethical and practical challenges of conducting experimental research with this population [26,27]. Research has been constrained by small sample sizes, uneven comparison group sizes, singular outcomes, lack of control groups, lack of randomization, and non-blind assessment [3,28].…”
Section: Introductionmentioning
confidence: 99%
“…Since 2015, many umbrella reviews have been conducted evaluating the evidence base on the psychosocial epidemiology of mental health in diverse populations [22][23][24][25][26][27]. Although several reviews have reported psychological impacts of quarantine or isolation [28,29], no umbrella review or overview of the reviews was found, which can inform the mental health implications of quarantine and isolation at the global landscape.…”
Section: Introductionmentioning
confidence: 99%